Econometric and comparative risk assessment scenario modelling of the proposed UK sugary drink tax on health - Briggs, A; Mytton, O; Elhussein, A; Scarborough, P (Lancet, 2016)
In March, 2016, the UK Chancellor of the Exchequer announced a two-tier industry levy on sugar-sweetened beverages (SSBs). We aimed to estimate the effect of possible industry responses on incidence of diabetes, obesity, and dental caries to inform design and implementation of the legislation.